1997
DOI: 10.1038/sj.ejcn.1600450
|View full text |Cite
|
Sign up to set email alerts
|

Daily energy expenditure and physical activity assessed by an activity diary in 374 randomly selected 15-year-old adolescents

Abstract: Objectives: To assess the average daily levels of physical activity, energy expenditure and the time and energy spent at different activities in two cohorts of Swedish adolescents. Design: Total energy expenditure (TEE) and physical activity level (PAL TEE/basal metabolic rate (BMR)) were estimated in 374 randomly selected healthy adolescents living in two different regions of Sweden on the basis of a seven-day activity diary (AD) and predicted BMR. A validation of the estimates from the AD with the doubly lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
47
3
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 10 publications
10
47
3
3
Order By: Relevance
“…The mean calculated PAL (1.64) of girls was lower than that of boys, and similar to those obtained by Bandini et al (1990), Davies et al (1991) and Ekelund et al (2000). However, it was lower than the values obtained by Bratteby et al (1997aBratteby et al ( ,b 1998. In the latter studies, adolescents were generally more active than our subjects, since 80 vs 12% of them walked or bicycled to and from school, and 62% of them trained regularly.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The mean calculated PAL (1.64) of girls was lower than that of boys, and similar to those obtained by Bandini et al (1990), Davies et al (1991) and Ekelund et al (2000). However, it was lower than the values obtained by Bratteby et al (1997aBratteby et al ( ,b 1998. In the latter studies, adolescents were generally more active than our subjects, since 80 vs 12% of them walked or bicycled to and from school, and 62% of them trained regularly.…”
Section: Discussionsupporting
confidence: 84%
“…The mean DEE of the 15-y-old boys (1.73) was lower than those obtained in the USA (Bandini et al, 1990), in the UK (Davies et al, 1991), and in Sweden (Bratteby et al, 1997a(Bratteby et al, ,b,1998Ekelund et al, 2000). However, the mean DEE expressed per kg BW or per kg FFM was intermediate between these values, and the differences were less than 6%.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Engstro Èm (1989) reported, based on questionnaire data, a gradual decline from 1968 to 1984 in participation in organized sports and leisure time spontaneous physical activity in 15 y old Swedish adolescents. On the other hand, Bratteby et al (1997) concluded, by using activity diary data, that Swedish 15 y olds have a high energy expenditure and a high physical activity level. To what extent Swedish adolescents achieve appropriate levels of physical activity in relation to existing physical activity recommendations is not known.…”
Section: Introductionmentioning
confidence: 99%